2020
DOI: 10.1186/s12909-020-02027-2
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety levels among health sciences students during their first visit to the dissection room

Abstract: Background: The teaching of human anatomy is often based on practices of cadaver dissection and prosected specimens. However, exposure to human cadavers might be stressful and anxiety-inducing for students. The aim of this study is to explore the degree of satisfaction and anxiety among first-year students in the Medicine, Occupational Therapy, Speech Therapy and Nursing programmes at the Universidad de Castilla-La Mancha (Spain) who are experiencing their first dissection/prosection practice to develop stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 47 publications
0
24
0
1
Order By: Relevance
“…Empathy is the emotional ability to understand the feelings of others so that they can see a problem from the other person's point of view. This concept is a form of emotional intelligence characterized by the ability to listen to a speech, accept viewpoints, feel the feelings of others based on changes in expression, tone of speech, and body language [5], [33], [34]. Empathy is the behavior of being conscious and reacting mentally and emotionally to others, feeling sympathy and concern for others, especially in others who are suffering by putting themselves in that other person's position so that others seem to be a part of him.…”
Section: It Builds Empathy For Patientsmentioning
confidence: 99%
“…Empathy is the emotional ability to understand the feelings of others so that they can see a problem from the other person's point of view. This concept is a form of emotional intelligence characterized by the ability to listen to a speech, accept viewpoints, feel the feelings of others based on changes in expression, tone of speech, and body language [5], [33], [34]. Empathy is the behavior of being conscious and reacting mentally and emotionally to others, feeling sympathy and concern for others, especially in others who are suffering by putting themselves in that other person's position so that others seem to be a part of him.…”
Section: It Builds Empathy For Patientsmentioning
confidence: 99%
“…Another potential factor affecting student burnout and anatomical self-efficacy is the frequent exposure to cadaveric tissue and body donors. Gross anatomy may be a student’s first experience with death and the emotional toll of navigating the topic of dying, and entering a dissection room can be challenging for some students [ 34 ]. Allison et al [ 35 ] found that medical students with increased fear of death had significantly lower performance on gross anatomy laboratory practical examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, biosafety measures are essential to maximize academic development with the safety of users, including students, professors, technicians and the cleaning staff ( Neto and Colombo, 2015 ). Furthermore, the handling of human corpses and their parts requires ethical, legal and technical qualities from users ( Elizondo-Omaña et al, 2004 ; Evans and Watt, 2005 ; Arráez-Aybar et al, 2014 ; Romo-Barrientos et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%